Modelling-Augmented Failure Diagnostics in Planar SiC MOS Devices Using TDDB Measurements - Cornigli, Davide; Schlichting, Holger; Becker, Tom; Larcher, Luca; Erlbacher, Tobias; Pešić, Milan (Solid State Phenomena, 2024)
In this study we analyzed the physical mechanisms governing time-dependent dielectric breakdown (TDDB) and we used TDDB physical model of dielectric breakdown, implemented in the defect-centric Ginestra® modeling platform, to deconvolute the intrinsic material properties effects and geometry feature impact on the gate oxide (GOx) and SiC-device breakdown.<br
Keywords: 4H-SiC; Defects; Gate Oxide; Modeling; Reliability